A Conceptual Model for Ethical Leadership in International IT Project Management (International Journal of Scientific Research in Science and Technology, 2024)
In the context of international IT project management, ethical leadership is crucial for ensuring project success, stakeholder trust, and the alignment of business practices with global standards. However, the complexity of managing cross-cultural, multinational teams in the IT sector presents unique challenges to ethical decision-making and leadership. This proposes a conceptual model for ethical leadership in international IT project management, aiming to provide a structured approach to addressing these challenges while fostering an ethical organizational culture. The model draws on key ethical principles, including integrity, transparency, accountability, and fairness, tailored to the global nature of IT projects. It integrates leadership theories and decision-making frameworks to guide project managers in navigating diverse cultural expectations, managing ethical dilemmas, and promoting responsible stakeholder engagement. The model emphasizes the importance of transparent communication, ethical decision-making frameworks, and accountability mechanisms in ensuring that ethical standards are upheld throughout the project lifecycle. Special attention is given to cultural sensitivity and the need for a balanced approach to ethical relativism and universal ethical norms in global contexts. Moreover, the conceptual model highlights key ethical challenges specific to international IT projects, such as corruption, data privacy, environmental responsibility, and the equitable treatment of stakeholders. Through case studies, this illustrates practical applications of the model, showcasing real-world examples of how ethical leadership can successfully address these issues and contribute to project success. This concludes by outlining the implications of ethical leadership in international IT project management and suggesting avenues for future research. By providing a framework for ethical leadership, this model serves as a valuable tool for project managers aiming to navigate the complex ethical landscape of global IT projects while fostering a culture of integrity and responsibility.